2021
DOI: 10.1186/s12904-021-00839-7
|View full text |Cite
|
Sign up to set email alerts
|

Same, same, but different? A longitudinal, mixed-methods study of stability in values and preferences for future end-of-life care among community-dwelling, older adults

Abstract: Background End-of-life preferences may change over time, e.g. due to illness progression or life events. Research on stability of end-of-life preferences has largely focused on life-sustaining treatments in seriously ill patients or medical decision-making based on hypothetical illness scenarios and possible treatment options. Few studies focus on community-dwellers in natural settings. The aim of this study was thus to explore if and how community-dwelling, older adults’ prioritizations and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The GoWish cards have been used in research studies with community‐dwelling adults in several countries [10, 15, 27, 28] and as the DöBra cards with majority populations in Sweden [4, 9, 17, 18], however, we have seen no other studies that have reported an extensive use of wild cards as in the present study. This may be in part due to interviewers explicitly prompting interviewees about other potential preferences not covered by card items.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The GoWish cards have been used in research studies with community‐dwelling adults in several countries [10, 15, 27, 28] and as the DöBra cards with majority populations in Sweden [4, 9, 17, 18], however, we have seen no other studies that have reported an extensive use of wild cards as in the present study. This may be in part due to interviewers explicitly prompting interviewees about other potential preferences not covered by card items.…”
Section: Discussionmentioning
confidence: 81%
“…The cards have been found to be feasible facilitators of conversations about values and preferences for EoL care, as well as useful for triggering general discussions about death and dying [9]. Eneslätt et al's research has pointed to the importance of considering how people reason about card statements, as this can vary by individual with regard to the same statement, and how wild cards are used to communicate individual values [4,18].…”
Section: Introduction and Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…Games have been shown to lower reluctance and resistance when discussing potentially uncomfortable topics such as death, dying, and end-of-life care [6] and can thus be helpful in supporting individuals in thinking and talking about ACP and end-of-life values and preferences. One card game that has shown positive results in stimulating discussion in various studies is the American Go Wish card game (developed the mid 90s by Coda Alliance, a U.S.-based non-profit organization) [7][8][9][10][11][12][13][14][15][16][17][18]. The card game consists of preformulated statements to initiate and support ACP discussions by identifying values and preferences about end-of-life issues and death and dying.…”
Section: Open Accessmentioning
confidence: 99%